Social Entrepreneurship - Innovative Solutions' Provider to the Challenges of an Ageing Population: The Case of Romanian Retirees - Mariana Dragusin; Dianne H. B. Welsh; Raluca Mariana Grosu; Alina Elena Iosif; Ion Daniel Zgura (Amfiteatru Economic Journal, 2015)
As an emerging field of practice and investigation Social Entrepreneurship (SE) provides many opportunities and challenges. This paper is exploring specific insights of the concept, including its fine borders with two other related terms: social economy and social enterprise. It also outlines steps forward in the process of enhancing SE eco-systems at both E.U. and national levels in order to provide transformational and innovative solutions to complex issues, like that of a fast growing ageing population, having strong social, economic and political implications. As a highly vulnerable social group, Romanian Retirees are the focus of the paper authors' experimental pilot model for social innovation and change - Senior Active Platform (S.A.P.), that can lead to their improved economic and social inclusion. Based on in depth desk research and an exploratory survey, main coordinates (mission, objectives, main stakeholders' benefits, business model etc.) of S.A.P. are identified and set up. Further needed pieces of research are outlined in order to refine the model and transform it into a replicable one in countries with similar background.
Keywords: M10; 330; social entrepreneurship; social economy; social enterprise; silver economy; retirees; social inclusion